The Spelling System in the Buku Katan Kamus Melayu - Tuan Besar, Tuan Zaifatul Akmal (2004)
This research is done to obtain imformation on the spelling system in the ‘Buku Katan Kamus Melayu’. Research instrument is ‘Buku Katan Kamus Melayu’ written by Major Datuk Haji Mohd Said Haji Sulaiman, published in 1936. Other books related to the instrument are ‘Pedoman Ejaan Jawi Yang Disempurnakan’ published by Dewan Bahasa dan Pustaka in 1986 (2nd Edition:1993– 3rd Edition) and ‘Pedoman bagi Hejaan’ written by Major Datuk Haji Mohd Said Haji Sulaiman, published by P.Bm.P.B. Diraja Johor in 1936. Findings have shown that there is a big difference in these both Jawi spelling being studied that is Jawi spelling system found in ‘Buku Katan Kamus Melayu’ by Major Datuk Haji Mohd Said Haji Sulaiman and the spelling system in ‘Pedoman Ejaan Jawi Yang Disempurnakan.’ The findings also show that Major Datuk Haji Mohd Said Haji Sulaiman has used an old spelling system which is influenced by the Arabic spelling system and this system causing confusion in the consumers. The suggestions brought forward include the exposure of the new spelling system as contained in ‘Pedoman Ejaan Jawi Yang Disempurnakan’ to students. The usage of spelling system of Jawi spelling system also need to be expanded especially by teachers in primary and secondary schools and followed by in educators higher level institutions. Jawi writing users should also be encouraged to used the new Jawi spelling system (Pedoman Ejaan Jawi Yang Disempurnakan) in their writing.